Satisfaction of basic psychological needs of young Serbian female athletes: the role of coach and teammates - Jovana Trbojević; Jelica Petrović (University of Novi Sad, Faculty of Sport and Physical Education, 2020)
In youth sport, coach and teammates have a relevant role in an athlete's development as a player. They can create a task or ego-involving motivational climate, and directly influence athlete's affective, cognitive, and behavioral outcomes. The purpose of this research is to examine the effects of motivational climate created by coach and teammates on the satisfaction of basic psychological needs in sport of young female athletes. The sample consisted of 192 young Serbian female athletes from collective sports (handball, volleyball, and basketball) with an average age of 13.6 years. They filled out Peer Motivational Climate in Youth Sport Questionnaire - MCYSQ (Ntoumanis & Vazou, 2005), Perceived Motivational Climate in Sport Questionnaire - 2 - PMCSQ-2 (Newton, Duda & Yin, 2000), and the Basic Need Satisfaction in Sport Scale (BNSSS, Ng, Losdale, & Hodge, 2011). Results of regression analysis showed that motivational climate created by coach and teammates represent significant predictors of the basic psychological needs: need for relatedness (35.5% of variance), need for competence (21.9% of variance), and need for autonomy - choice (10.5% of variance). Perceived task-involving motivational climate created by coach and teammates singled out as statistically significant predictors of need for relatedness and competence, while task-involving motivational climate created by teammates singled out as significant predictor of need for autonomy. Athletes who perceive coach's and teammate's behavior as task-involving, will have more satisfied basic psychological needs. Understanding the factors that facilitate basic needs contribute to prevention of dropping out of sports in adolescence, and athlete's motivation and achievement.